Anaesthetic effects of xylazine combinations in high and low concentrations of tiletamine-zolazepam, with and without ketamine, in cats - Chen, Hui Cheng; Chee, S. K. (Veterinary Association Malaysia, 2005)
Intramuscular (1M) administration of four anaesthetic combinations were evaluated on nine cats ina repeated manner. The anaesthetic regimens were: (i) 2 mg/kg tiletamine, 2 mg/kg zolazepam, 3.2 mg/kg ketamine and 0.8 mg/kg xylazine (T₄KX); (ii) 1 mg/kg tiletamine, 1 mg/kg zolazepam, 3.2 mg/kg ketamine and 0.8 mg/kg xylazine (T₂KX); (iii) 2 mg/kg tiletamine, 2 mg/kg zolazepam and 0.8 mg/kg xylazine (T₄X); and (iv) 1 mg/kg tiletamine, 1 mg/kg zolazepam and 0.8 mg/kg xylazine (T2X). All four combinations induced smooth recumbency within 4 minutes following IM administration and enabled intubation. All four anaesthetic combinations caused an immediate increase in heart rate and a dramatic decrease in respiratory rate. Pale to slight cyanotic mucous membrane was observed in most cats, 5 minutes following administration of any of the anaesthetic combinations. The T₄KX combination provided the longest duration of anaesthesia, followed by T₂KX, T₄X and T₂X, Time from IM injection to righting reflex, sternal recumbency, and standing or walking, was longest after administration of T₄KX, followed by T₄X, T₂X and T₂KX. Quality of recovery from anaesthesia was better following T₂X and T₂KX administration compared to T₄X and T₄KX. This study demonstrates the benefits of adding ketamine in the anaesthetic combination to reduce the tiletaminezolazepam component. The data in this study can be used to compare and choose an initial IM TKX induction dose for short and non-invasive procedures in cats.